Palladium‐Catalyzed Enantioselective Allylic Substitution in the Presence of Monodentate Furanoside Phosphoramidites. Issue 5 (21st January 2015) - Majdecki, Maciej; Jurczak, Janusz; Bauer, Tomasz
Abstract A library of monodentate furanoside phosphoramidites, easily synthesized from inexpensive D‐xylose and optically pure 1, 1′‐bi‐2‐naphthol (BINOL), was used as ligands for the palladium‐catalyzed allylic alkylation and amination. The matched pair was formed from D‐xylose‐derivatives and (S)‐BINOL. The asymmetric induction depends strongly on the substituent at the C5 of the carbohydrate backbone; both bulky 5‐O‐pivaloyl and 5‐deoxy derivatives gave excellent results, whereas ligands with trityl protection at position C5 induced low ee values with reversal of configuration. The solvent used for the addition is also of great importance with highest enantioselectivities observed in diethyl ether. The best results for both alkylation and amination, up to 98–99 % ee, were obtained for sterically demanding allylic acetates.